Antibacterial Activity of the Original Dietary Supplement Oxidal® in Vitro (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Studies have been conducted to determine the antibacterial effect of Oxidal® and anolyte against Staphylococcus aureus and Escherichia coli. The bacterial strains tested showed high sensitivity to the dietary supplement Oxidal® and to anolyte, as well as to the control antibiotic Thiamphenicol. The mean MPC50 values of Oxidal® for Gram-positive bacteria S. aureus (0.21 ± 0.13 mg/ml) were lower than those for Gram-negative E. coli (0.55 ± 0.24 mg/ml). The dose that fully suppressed S. aureus growth was 0.86 ± 0.52 mg/ml, while for E. coli this dose was significantly higher - 2.40 ± 0.80 mg/ml (P